A review on robot motion planning approaches - Tang, Sai Hong; Khaksar, Weria; Ismail, Napsiah; Mohd Ariffin, Mohd Khairol Anuar (Universiti Putra Malaysia Press, 2012)
The ability of a robot to plan its own motion seems pivotal to its autonomy, and that is why the motion planning has become part and parcel of modern intelligent robotics. In this paper, about 100 research are reviewed and briefly described to identify and classify the amount of the existing work for each motion planning approach. Meanwhile, around 200 research were used to determine the percentage of the application of each approach. The paper includes comparative tables and charts showing the application frequency of each approach in the last 30 years. Finally, some open areas and challenging topics are presented based on the reviewed papers.